Liangcoris, a new genus of Harpactorinae (Hemiptera: Reduviidae) from China - Zhao, Ping; Cai, Wanzhi; Ren, Dong (Zootaxa, 2007)
Liangcoris yangae Zhao, Cai & Ren, gen. & sp. nov. of the subfamily Harpactorinae from China, is described and illustrated. A key to closely related genera is provided.